Improving Student Reading Interest by Cultivating Early Literacy at SDN 1 Pagar Air: A Literature Review - Halimah Halimah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study delves into the enhancement of students' reading interest through the fostering of early literacy at SDN 1 Pagar Air. The research employs a library research methodology to analyze existing literature on early literacy practices and their impact on developing reading interest among elementary school students. Through a comprehensive review of relevant studies, the paper identifies key strategies and approaches that have been effective in promoting reading engagement at a young age. The findings underscore the importance of cultivating a reading culture within educational institutions and the role of teachers, parents, and the community in supporting early literacy initiatives. This research aims to provide insights and recommendations for educators and policymakers to implement effective literacy programs that instill a lifelong love for reading in students.